Pandemic of Covid-19 in Indonesia : Social Politics Perspective - Shindy Diah Ayu Lestari (Journal of Development and Social Change, 2021)
In the second half of the twentieth century, global security issues have quickly transformed into what is defined nowadays as non-traditional security issues, such as the recent Covid-19 pandemic which impacted the whole world. It has changed the paradigm of life in almost every sector including sensitive matters such as religious activities that have been mentioned as a human right previously.  Different cultural backgrounds means that the current circumstances cannot be handled the same way for every country. Eastern countries with their high social interactions caused faster initial spreading mostly from the mobilization. Specific matter like “mudik” during pandemic that happened near Ramadhan is another challenging issue for Indonesia, as the highest populated Moslem country. Using the problems arising from the progression of pandemic in Indonesia, the present work aim to assess the major difficulties faced by the country in order to establish a set of short and long term plans that should be addressed to improve the preparedness against such pandemics and correct the current flaws that created difficulties to develop an optimal response. Governmental decisions should be quick, clear and follow a solid strategy to ensure the population is aware that the cases are continuing to increase and apply the effects of the social distancing measures that have been put in place. Not only healthcare, but economic, social and political issues need to be planned  during and after pandemic to build solid and better foundations for future development of the Republic of Indonesia.